Pengembangan Multimedia Pembelajaran Interaktif Berbasis Macromedia Flash 8 pada Mata Pelajaran SKEP di Kota Cilegon - Juliarni Clarisa; Irwanto Irwanto; Didik Aribowo (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
The creation of the 2013 curriculum for YPWKS Vocational High School students in the 2019/2020 school year. The study program promotes student competency development through SKEP (Electrical Pneumatic Control System) disciplines. Based on observations from oral interviews, there was no multimedia learning to assist learning in these subjects, therefore the goal of this research is to support learning in SKEP subjects. The development research, or R&D (Research and Development), was carried out utilizing the Borg and Gall model, which was reduced from 10 to 7 stages. The model is divided into seven stages: one for research analysis and data collection, two for planning, three for product draft development, four for initial field trials, five for revising test results, six for product outcomes refining, and seven for dissemination and implementation. Three material experts and three media experts are involved in the feasibility of multimedia learning. Then the multimedia was tested on class XI students of the Industrial Automation Engineering competence program and the scale used in gauging the "Likert scale". Based on the results of validation by media experts and material experts, the feasibility of interactive learning multimedia in the media aspect was 73.99 (very good) from a score range of 65.00 X 80.00, and the feasibility of the material aspect was 58.99 (very good) from a score range of 52.00 X 64.00. Field According to trial data, students responded to the practicality of Interactive Learning Multimedia with an average score of 50% (very good) on a scale of 0-100%. These findings suggest that the created Electropneumatic Control System Learning Multimedia is appropriate for use in Electropneumatic Control System Learning activities, particularly for students in class XI Industrial Automation Engineering studying Pneumatic Control System material.